ANALYSIS OF THE LACK OF PUBLIC KNOWLEDGE REGARDING THE DEVELOPMENT OF ISLAMIC BANKING IN INDONESIA - Sofwan Alwi; Siti Afidatul Khotijah (Transpublika Publisher, 2022)
The writing of this article aims to analyze the lack of public knowledge of the development of Islamic banking in Indonesia. The literature review method with a descriptive qualitative approach is a method applied to this study. A literature review is an approach that discovers, analyses, and interprets all data on a study topic used to answer queries and requests for previous research. The subject of this study is the holy book that explains and explains the challenges of Islamic bank development in Indonesian culture. The results of the research on existing literature will discuss the development of Islamic banking as well as the gap between the theory and practice of understanding society and Indonesian people perspective towards Islamic banks. The findings of the study are expected to show conclusions about the causes of the lack of public understanding of the development of Islamic banking in Indonesia.